BIOGAS PRODUCTION IN DAIRY CATTLE SYSTEMS, USING BATCH DIGESTERS WITH AND WITHOUT SOLIDS SEPARATION IN THE SUBSTRATES - Anjos, Isis dos; Toneli, Juliana T. C. L.; Sagula, Alex L. [UNESP]; Lucas Junior, Jorge de [UNESP] (Soc Brasil Engenharia Agricola, 2017)
This research aimed to evaluate the biogas production during the anaerobic biodigestion process of dairy cattle manure, with and without solids separation. Sixteen biodigesters of the batch type were used, each one with 2L of capacity, supplied with manure in four different conditions: (1) pure manure, after washing the floors of the free stall system; (2) manure after the solids separator; (3) manure after the solids separator and sand decanter and (4) manure with the solid retained in separator solids, dissolved in water. The hydraulic retention time was of 196 days. The highest reductions of volatile solids (VS) were obtained for the biodigesters supplied with manure that went through some process of solids separation. The highest potential of methane production(CH4) obtained was of 0.2686 m(3) CH4 kg(-1) of added VS, supplied to digesters with manure after solids separator. The best potential for biogas and methane production was observed when there was a reduction of the solids concentration in the manure and, in this case, the hydraulic retention time can be reduced, which reduces the volume of the biodigester and the cost of implementation and maintenance, but the highest biogas production occurred in the biodigesters without solids separation.
Keywords: biogas; biodigester; manure; dairy cattle; solid separation